Fluorescence properties of self assembled colloidal supraparticles from CdSe/CdS/ZnS nanocrystals. (30th November 2020) - Blondot, Victor; Bogicevic, Alexandra; Coste, Antoine; Arnold, Christophe; Buil, Stéphanie; Quélin, Xavier; Pons, Thomas; Lequeux, Nicolas; Hermier, Jean-Pierre
Abstract: We first report the synthesis of supraparticles with a mean diameter of 130 nm consisting in a compact self-assembly of colloidal CdSe/CdS/ZnS nanocrystals encapsulated in a silica shell. This provides a system with robust optical properties such as a high quantum efficiency, a stable and Poissonian emission at room temperature. Additionally, enhancement of the photoluminescence decay rate through Förster resonance energy transfer is observed.